Efficacy and safety of apalutamide, abiraterone acetate, and bicalutamide in the treatment of metastatic hormone-sensitive prostate cancer - Zhang, Jiabin; Wang, Qiang; Zhou, Junjie; Gao, Huiyu; Hao, Peng; Wu, Tao (Frontiers in Oncology, 2025)
ObjectivesTo compare the efficacy and safety of three drugs—Apalutamide, Abiraterone, and Bicalutamide—combined with Androgen Deprivation Therapy (ADT) in patients with metastatic hormone-sensitive prostate cancer (mHSPC).MethodsWe retrospectively collected survival data of patients treated at our hospital from January 2019 to March 2024. Patients who received three different treatment regimens—Apalutamide (240 mg/day) combined with ADT, Abiraterone (1000 mg/day) plus Prednisone (5 mg/day) combined with ADT, and Bicalutamide (50 mg/day) combined with ADT.ResultsThis study analyzed 146 mHSPC patients. The results are displayed that Apalutamide and Abiraterone significantly prolonged PFS and PSA-PFS compared to Bicalutamide. Univariate and multivariate COX regression analyses suggested that factors such as age <75 years, absence of lymph node metastasis, use of Apalutamide or Abiraterone, and a low ECOG score were associated with longer PFS. Moreover, Apalutamide and Abiraterone showed superior efficacy in improving PSA response compared to Bicalutamide. Importantly, no life-threatening adverse events were reported in any of the three treatment groups.ConclusionCompared to Bicalutamide, the novel endocrine therapies Apalutamide and Abiraterone both significantly prolong PFS, PSA-PFS, and improve PSA response rates.